PENERAPAN KOMBINASI PUPUK ORGANIK DAN PUPUK KIMIA UNTUK MEMPERBAIKI KUALITAS TANAH SAWAH DI SUBAK TIBUBIYU KECAMATAN KERAMBITAN KABUPATEN TABANAN - Narka, I.W.; Kusmawati, T.; Merit, I.N.; Dibia, I.N. (Buletin Udayana Mengabdi, 2018)
Community service with the title of the application of the combination of organic fertilizer and chemical fertilizer to improve soil quality in Subak Tibubiyu Sub-district of Kerambitan, Tabanan Regency was carried out. Farmers using an excessive inorganic fertilizers with lead to the degradation of soil quality. While the use of organic fertilizers alone without the use of chemical fertilizers can also decrease the yield significantly. To maintain the quality of the soil and the yield production in good manner is recommended to combine the use of organic manure and inorganic fertilizers. Implementation of activities begins with how to gather the leaders of society and a member of the subak, will then be given a guidance about fertilizing by using a combination of organic and unorganic fertilizer. In addition to the extension it is also created a demonstration plot about the use of inorganic and organic fertilizers in combination trial. The results of the activities showed that the farmers and community leaders was welcomed to this activity. Farmers are very enthusiastic about this topic. Farmers was interested in using a combination of organic and unorganic fertilizer. They produce organic fertliuzer using in situ materials such as : green manure, rice straw,etc. Using the combination of these fertilizer is suppose to be decrease the real cost which spent by farmer.